Precision‐Guided Munitions - Maini, Anil K (Handbook of Defence Electronics and Optronics, 2018)
This chapter presents a brief introduction to precision‐guided munitions (PGMs). It focuses on guidance techniques employed in this class of weapons, different types of PGMs in terms of involved technologies, capabilities and limitations, deployment configurations, state‐of‐the‐art and future trends. The PGMs include the laser‐guided munitions, infrared (IR)‐guided weapons, radar‐guided weapons and GPS/ INS‐guided weapons. The chapter discusses the different guidance techniques: beam rider guidance, command guidance, homing guidance and navigation guidance. Major performance parameters of laser‐guided munitions include sensitivity, field‐of‐view, PRF code compatibility and response linearity. Different deployment configurations are used for laser‐guided munitions delivery depending upon the nature of mission. Pulse repetition frequency (PRF) code compatibility check forms the basis of identification of the desired radiation and is therefore essential to weapon's functionality and mission success. Laser‐guided munitions are broadly categorized as surface‐launched projectiles, aerially delivered bombs and surface‐to‐surface, surface‐to‐air and air‐to‐surface missiles.